Nilai-Nilai Pendidikan Islam pada Indigenus Knowledge of Mangawah Culture: Analisis Validitas dan Realibilitas Instrumen Wawancara pada Acara Bahaul Barito Utara - Ais Anggraini, Puspita; Supriatin, Atin; Santiani, Santiani (UIR Press, 2025)
This research aims to determine the validity and reliability of the interview instrument related to Islamic Educational Values in the Indigenous Knowledge of Mangawah Culture: Analysis of the Validity and Reliability of the Interview Instrument in the Bahaul North Barito Event.. The approach used is exploratory qualitative. To calculate validity and reliability, Microsoft Excel was utilized. The results of the validity test show that the instrument achieved a feasibility score of 85% and a validity score of 66.96%, which according to Arikunto's criteria falls into the 'feasible' category. Meanwhile, the reliability test results indicate a Cronbach Alpha value of 0.808, which based on Sugiyono's criteria (2017) is classified as very high reliability. Based on the results, it can be concluded that the interview instrument used in this study has met the standards of validity and reliability, making it suitable for collecting data on the values of Islamic education in the mangawah tradition during the bahaul event in Jambu Village, Barito Utara Regency.